2012
DOI: 10.4236/ojemd.2012.24013
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Quercus Infectoria Gall Extract on Osteoblast Function and Bone Metabolism

Abstract: The galls of the Quercus infectoria (QI) tree are traditionally believed to have great medicinal value. Pharmacologically the galls are claimed to have various biological activities such as astringent effect, antidiabetic, antitremorine, local anaesthetic, antipyretic, anti-inflammatory, antibacterial, antiviral and many more. These pharmacological activities of gall extracts were reported to be due to its excellent antioxidant activity with phytochemicals constituents of phenolic and flavanoid compounds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
10
0
2
Order By: Relevance
“…[30,31] Polyphenols in QI gall extracts also exhibit anticancer activities in different in vitro models. [22,29,32] Chemopreventive effects of QI against Fe-NTA-induced renal carcinogenesis, inhibition of hyperproliferative response, and diminish oxidative stress were demonstrated by the study done by Rehman et al [33] Wound Healing Activity Animal studies have shown a definite wound healing activity in ethanol extracts of Majuphal. There has been a significant increase in activities of various enzymes associated with wound healing.…”
Section: Antioxidant Activity and Anticancer Activitymentioning
confidence: 99%
“…[30,31] Polyphenols in QI gall extracts also exhibit anticancer activities in different in vitro models. [22,29,32] Chemopreventive effects of QI against Fe-NTA-induced renal carcinogenesis, inhibition of hyperproliferative response, and diminish oxidative stress were demonstrated by the study done by Rehman et al [33] Wound Healing Activity Animal studies have shown a definite wound healing activity in ethanol extracts of Majuphal. There has been a significant increase in activities of various enzymes associated with wound healing.…”
Section: Antioxidant Activity and Anticancer Activitymentioning
confidence: 99%
“…The plant was reported to have alkaloids, flavonoids, saponins, steroids, triterpenoids, and tannins. 8,9 Casturi's bark contains saponins, steroids, and tannins, which have antibacterial properties against S. mutans, 10 S. aureus, and E.coli. 11 The tannins contained in 127.42 grams of Mangifera casturi bark extract is 8.5%.…”
mentioning
confidence: 99%
“…Tannins were reported to have effect in increasing the osteoblast's activities and suppressing the osteoclast's activities. 9 The increase of osteoblast's activities by alkaloids and polyphenols such as tannins is because the induction of IL-1β and BMP-2 expressions on wound site. 13 Secondary substances such as polyphenols in foods and plants, one of them being Mangifera casturi, can help bone tissues repair by increasing the osteoblast's activities and suppressing the osteoclast's activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also ointments with powders of galls incorporated in to it as a local application for these anal diseases 3 . Sometimes, the galls are recommended as an antidote for plant poisons due to opium, nux vomica and aconite 4 .…”
mentioning
confidence: 99%